Assessment of knowledge and perception about LGBTQ+ community in Indian medical students - Kimmatkar, Ankush; Devaragudi, Sanjana; Kolte, Roohi; Shahi, Harsha; Pradeep, Anju; Sangaraju, Sai Lahari; Mandavkar, Anuja (International Journal of Research in Medical Sciences, 2025)
Background: The LGBTQ+ community in India is underrepresented and face significant social challenges. The medical students and graduates in the country have limited educational material and training on the community’s healthcare needs. This can lead to bias in treatment and substandard patient care. The objective of this study was to assess the knowledge, education, and training, and perception of the LGBTQ+ community among Indian medical students and graduates. Methods: A three-month cross-sectional survey-based study was conducted among Indian medical students and graduates using a Google form questionnaire to assess their knowledge, training, and perceptions about the LGBTQ+ community. The data were collected using Google sheets and analysed using Microsoft excel. Results: Only 43% of the 546 participants had read about LGBTQ+ health in their medical school; however, 90% had used online platforms for learning. The majority agreed that more educational material was necessary, and nearly 90% perceived a need to bridge the knowledge gap on LGBTQ+ health concerns in the medical curriculum. Additionally, almost 90% of participants also felt that social support groups for the LGBTQ+ community were necessary, and educational institutions should provide sexual education for all orientations. Participants who had poor self-perceived knowledge about LGBTQ+ health had a significantly lower mean score on the knowledge assessment questionnaire than those who perceived their knowledge to be good. Conclusions: Medical students and graduates in India need to receive adequate training and educational material on LGBTQ+ related health to improve their confidence in addressing healthcare issues and reduce bias towards the healthcare needs of the LGBTQ+ community.